Penggunaan Bahasa Gaul dalam Komunikasi Digital pada Konten Tiktok Nathalie Tresya - Avida Alfi Atuzzahro; Dinar Thahira Handatika; Ayunda Riska Puspita (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to examine in depth the use of slang in digital communication by TikTok Gen Z content creator, Nathalie Tresya. Slang as a form of language variation reflects social dynamics, generational identity, and popular culture trends that develop in the digital space. This study uses a qualitative descriptive approach with a non-participatory observation method. Data were collected from a number of TikTok videos uploaded by Nathalie Tresya, focusing on verbal and textual speech containing slang elements. Analysis was conducted to identify the form, function, and context of slang use in the content studied. The results of the study show that Nathalie Tresya uses various forms of slang such as abbreviations, puns, foreign loanwords, and code mixing between Indonesian and English. This language is used as a communication strategy to build closeness with the audience, display identity as part of Gen Z, and increase the appeal of content on the TikTok platform. These findings confirm that social media, especially TikTok, is a medium that actively encourages the birth of new language forms that are worthy of being studied in the context of digital sociolinguistics.